The Early Mediaeval Slav-German border (Limes Sorabicus) in the light of research into Y-chromosome polymorphism in contemporary and historical German populations - Kowalski, Mariusz. Autor (IGiPZ PAN, 2020)
In the 8th century, the first political boundary between Germany (the land of the Franks) and the Slav people – known as Limes Sorabicus – followed the line of the Rivers Elbe and its tributary the Saale. In later centuries this was breached under the influence of an eastwards political expansion of Germany also characterised by developing German colonisation in that same direction (of the so-called Ostsiedlung). The consequence was for German regional communities to take shape to the east of the old Limes Sorabicus. Alongside the emigrants from the west, further participants in the process where autochthonous Slavs and Balts. This mixed origin of the new communities arising is revealed in historical accounts, but also via the results of scientific analyses of various profiles. The genetic research carried out to date supports the above contention, as well as a conclusion that the zone around the old Limes Sorabicus, despite its running through the centre of what is today an ethnically-German area, continues to represent a separation of populations whose ancestors are mainly of distinct origins.
24 cm
Keywords: Germanie (lud); Słowianie; kolonizacja w kierunku wschodnim; pochodzenie ludów; granice reliktowe; badania genetyczne